Crisis of habitus: the experiences of South Asian migrant managers and professionals in Australia - Mohyuddin, Syed; Pick, David (Society for Global Business & Economic Development (SGBED), 2011)
The aim of this paper is to examine the career experiences of managers and professionals who choose to migrate from South Asia (India, Pakistan, Sri Lanka and Bangladesh) to Australia. Using a combination of phenomenology and analysis of narratives, data was collected from 21 migrants through in-depth face-to-face interviews. Analysis of the data reveals a ‘crisis of habitus’ that leaves the participants with a sense of disembeddedness that prompts them to reconcile this crisis through processes of acculturation and sense-making. The analysis suggests that participants tended to make assumptions about their environment that often hindered their adaptation and career progression. While the research is limited to Australia, the results have wider significant theoretical and practical relevance. Applying the concept of habitus contributes to current understandings about the career challenges faced by migrants. This brings to light new and significant insights and have the potential to raise awareness amongst policy makers and business organisations.